MEMAHAMI PERSEPSI KONSUMEN TERHADAP PERSONALISASI PRODUK YANG DIPENGARUHI KECERDASAN BUATAN (AI GENERATIF) DI SERANG, BANTEN - Indar, Indar; Fuadi, Fuadi (Gapenas Publisher, 2025)
This study aims to analyze consumer perceptions in Serang, Banten, towards generative AI-based marketing personalization, focusing on factors of acceptance, concerns, and the influence of local culture. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 18 consumers who actively use digital platforms. The results show that while consumers value the benefits of AI personalization, such as relevant product recommendations and time efficiency, they also voice deep concerns regarding data privacy and system accuracy. Unique findings reveal a strong preference for local brands and the importance of digital literacy in shaping technology acceptance. This study provides practical recommendations for businesses, including increasing data transparency and a hybrid development model that integrates AI with human interaction. Limitations of the study include the limited number of participants and the geographic focus on one region, so further research is recommended to expand the scope with a mixed-method approach and cross-regional comparative studies. This study contributes to the understanding of the application of AI in marketing in the local context of Indonesia, especially in non-metropolitan areas such as Serang